Healthcare provider-to-patient perspectives on the uptake of teleconsultation services in the Nigerian healthcare system during the COVID-19 pandemic era - Ifeanyi Jude Ezeonwumelu; Ifeanyi Jude Obijiaku; Chukwudi Martin Ogbueche; Ucheoma Nwaozuru (Public Library of Science (PLoS), 2022)
The urgency to curtail the devastating effects of the ongoing COVID-19 Pandemic has led to the implementation of several measures to limit its spread, including movement restrictions and social distancing. As most developing countries rely solely on hospital visitations for their medical needs, this impediment to assessing healthcare services compounded by low uptake of telehealth services could result in dire consequences. This is a cross-sectional study among Healthcare providers (HCP) and Healthcare consumers (HCC) in Nigeria. We administered a pre-validated self-administered online questionnaire comprising questions to assess the knowledge, use, perceptions, and benefits of telemedicine among study participants. Descriptive statistics were used to examine participants' perceptions on telemedicine use and to summarize participants' characteristics. A total of 158 healthcare providers and 1381 healthcare consumers completed the online survey. Ninety percent of HCP reported that they used some form of telemedicine to deliver health care, and 63% of HCC had received healthcare through telemedicine. A significant proportion of HCP (62%) and HCC (69%) agreed that telemedicine would improve healthcare consultation experience and satisfaction. However, fewer (21%) HCP agreed that they liked that there would be no physical contact with patients using telemedicine. In contrast, 52% of HCC agreed that they liked that there would be no physical contact with healthcare providers while using telemedicine. The majority of the participants believed that benefits of telemedicine would include: being a safe way for healthcare delivery during pandemics (HCP = 62%, HCC = 83%), affordability (HCP = 62%, HCC = 82%), and time-saving (HCP = 54%, HCC = 82%,). Teleconsultation services have been shown to aptly complement face-to-face hospital visits in ensuring effective triaging in hospitals and providing adequate healthcare delivery to patients regardless of geographical and physical barriers. These results support telemedicine use for the provision of healthcare services during the COVID-19 pandemic.